2009
DOI: 10.1016/j.biomaterials.2008.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of hepatocyte phenotype in vitro via chemomechanical tuning of polyelectrolyte multilayers

Abstract: It is increasingly appreciated that since cell and tissue functions are regulated by chemomechanical stimuli, precise control over such stimuli will improve the functionality of tissue models. However, due to the inherent difficulty in decoupling these cues as presented by extracellular materials, few studies have explored the independent modulation of biochemical and mechanical stimuli towards the manipulation of sustained cellular processes. Here, we demonstrate that both mechanical compliance and ligand pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
90
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 43 publications
3
90
0
Order By: Relevance
“…These cells are widely considered to be ideal for constructing liver tissue models but are known to rapidly lose their viability (within a few hours or days) and phenotype functions upon isolation from the native in vivo microenvironment of the liver. They found that, on unmodified PAH/PAA surfaces, hepatocyte attachment increased with PEM rigidity, [195] but this trend was canceled when the PEM substrata was modified with COL I or with COL I pre-mixed with the small proteoglycan decorin (Fig. 7).…”
Section: The Role Of Film Mechanical Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…These cells are widely considered to be ideal for constructing liver tissue models but are known to rapidly lose their viability (within a few hours or days) and phenotype functions upon isolation from the native in vivo microenvironment of the liver. They found that, on unmodified PAH/PAA surfaces, hepatocyte attachment increased with PEM rigidity, [195] but this trend was canceled when the PEM substrata was modified with COL I or with COL I pre-mixed with the small proteoglycan decorin (Fig. 7).…”
Section: The Role Of Film Mechanical Propertiesmentioning
confidence: 95%
“…7B). [195] As previously described in Section 4.4, Picart et al developed an alternate strategy for tuning film mechanical properties using a simple water-based chemical cross-linking method applicable to PEM films that contain amine and carboxylic groups. For PLL/HA films, fine-tuning the EDC cross-linker concentration in contact with the films made it possible to vary the film's stiffness over two orders of magnitude.…”
Section: The Role Of Film Mechanical Propertiesmentioning
confidence: 98%
“…PAA/ PAH multilayers have been used to culture hepatocytes and these substrates appear to elicit increased urea and albumin production in comparison to hepatocytes cultured on a collagen surface. 102 Similarly, Wittmer et al have demonstrated that both PLL/ALG and PLL/PLGA PEMs facilitate adult rat hepatocyte adhesion and increased albumin production when compared to cells cultured on a collagen surface. 103 Further, in both reports, the adsorption of collagen on the terminal PE layer enhanced hepatocyte adhesion and phenotypic functions.…”
Section: Detzel Et Almentioning
confidence: 99%
“…103 Further, in both reports, the adsorption of collagen on the terminal PE layer enhanced hepatocyte adhesion and phenotypic functions. 102,103 Hepatocytes are generally stable when cultured between two collagen gels (collagen sandwich). 104,105 When these cells are cocultured with nonparenchymal hepatic cells, their function can be further enhanced.…”
Section: Detzel Et Almentioning
confidence: 99%
“…Many biomaterials have been developed for liver cell culture (Janorkar et al, 2008;Khetani and Bhatia, 2008;Chen et al, 2009;Pavlica et al, 2009;Feng et al, 2010;Kim et al, 2010;Mehta et al, 2010), but these too are limited by short term culture (typically 5-15 days) so that cell culture also is still a long ways from clinical application for BAL purposes. A number of nanofabrication scaffolds have been used for liver cell culture (Feng et al, 2010), but the solvents used for nanofabrication can be a toxic concern.…”
mentioning
confidence: 99%